Eksplorasi Proses Berpikir Komputasional Matematis SMP Siswa Ditinjau dari Disposisi Matematis: Studi Kasus Kualitatif - Syari, Aulia Kartika; Suyono, Suyono; Wiraningsih, Eti Dwi (Media Pendidikan Matematika, 2026)
This study aims to analyze students’ mathematical computational thinking skills in solving problems on Systems of Linear Equations in Two Variables (SPLDV) based on their levels of mathematical disposition. The study contributes to mathematics education research by demonstrating that mathematical disposition significantly shapes the depth and coherence of students’ computational thinking processes. A qualitative approach with a case study design was employed, involving two ninth-grade students from a junior high school in Depok City in the 2025/2026 academic year, each representing high and low levels of mathematical disposition. The research instruments consisted of a mathematical disposition questionnaire and a descriptive test of computational thinking skills developed based on four indicators: decomposition, abstraction, algorithmic thinking, and generalization. Data were analyzed through data reduction, data display, and conclusion drawing, with triangulation between test results and interviews to ensure credibility. The findings reveal that students with high mathematical disposition were able to fulfill nearly all computational thinking indicators in a systematic and reflective manner. In contrast, students with low mathematical disposition encountered difficulties particularly in decomposition, constructing algorithmic procedures, and making generalizations. These findings provide empirical evidence that differences in mathematical disposition are associated with variations in problem-solving structure and reasoning quality. Therefore, mathematics instruction should be designed to develop cognitive skills while simultaneously fostering positive learning dispositions.